'Kids in Design': Designing creative schools with children - Izadpanahi, Parisa; Xu, L.; Elkadi, H.; Ang, S. (2012)
There is a consensus that children should be involved in the planning and design process of their schools, and attempts have been made throughout the world. This paper introduces a 'Kids in Design' project, through which primary school children worked with university architecture students to design a school playground. The aim of the project was to encourage the full potential of children's creativity and generate creative school design outcomes. From October to December 2011, the 'Kids in Design' project was conducted in Roslyn Road Primary School (Geelong, Australia). Through eight weeks of workshops, children in Year 5 & 6 worked with architecture students from Deakin University (Geelong, Australia) to design a school playground. Assessing the design outcomes of this project, assertions are made that creative design outcomes have been achieved. Deakin University is currently working with another primary school to replicate the 'Kids in Design' project in 2012.